EXPERIENTIAL LEARNING SEBAGAI MODEL PEMBELAJARAN ALTERNATIF DI MADRASAH IBTIDAIYAH - M. Khairul Amri; Winsidi (Roqooba Journal of Islamic Education Management, 2022)
Among the learning alternatives that can be used to answer one of the problems in educationrelated to the learning experience is to use an experiential learning model which is almostsimilar to the scientific approach in thematic learning. Where thematic learning emphasizesmore on the application of the concept of learning by doing something (learning by doing).Therefore, teachers need to package or design learning experiences that will affect thesignificance of student learning. Learning experiences that show the relationship of theseconceptual elements make the learning process more effective. The conceptual relationshipbetween the subjects studied and will form a schema, so that students will gain knowledgeabout unity and unity. In addition, the implementation of thematic learning in elementaryschools will help students, because it is in accordance with the stage of development ofstudents who still see everything as a whole (holistic). Learning will provide opportunities forstudents to understand the complex problems that exist in the surrounding environment with acomplete view. With this thematic learning, students are expected to have the ability to identify,collect, assess and use the information around them in a meaningful way. This can be obtainednot only through the provision of new knowledge to students but also through the opportunityto strengthen and apply it in a variety of new situations that are increasingly diverse. Thus, theintegration in this thematic learning can be seen from the process aspect, curriculum aspect,and teaching and learning aspect.